Fine mapping of a novel QTL DM9.1 conferring downy mildew resistance in melon - Zhang, Xuejun; Ling, Yueming; Yang, Wenli; Wei, Minghua; Wang, Zhenzhu; Li, Meihua; Yang, Yong; Liu, Bin; Yi, Hongping; Guo, Yang-Dong; Kong, Qiusheng (Frontiers in Plant Science, 2023)
Abstract Downy mildew (DM) is a major foliar disease globally causing great economic loss in melon production. Utilizing disease-resistant cultivars is the most efficient approach for disease control, while discovery of disease-resistant genes is crucial for the success of DM-resistant breeding. To address this problem, two F2 populations were constructed using the DM-resistant accession PI 442177 in this study, and QTLs conferring DM resistance were mapped using linkage map and QTL-seq analysis, respectively. A high-density genetic map with the length of 1096.7 cM and density of 0.7 cM was generated by using the genotyping-by-sequencing data of a F2 population. A major QTL DM9.1 with the phenotypic variance explained proportion of 24.3-37.7% was consistently detected at the early, middle, and late growth stages using the genetic map. QTL-seq analyses on the two F2 populations also validated the presence of DM9.1. Kompetitive Allele-Specific PCR (KASP) assay was further carried out to fine map DM9.1 into 1.0 Mb interval. A KASP marker co-segregating with DM9.1 was successfully developed. These results not only provided valuable information for DM-resistant gene cloning, but also offered useful markers for melon DM-resistant breeding programs.